THE IMPACT OF TOOTH-CUTTING CEREMONY ON HIV SUFFERERS IN KLUNGKUNG REGENCY - Wayan Jaya Putra; I Nyoman Adiputra; I Made Sugata (UHN I Gusti Bagus Sugriwa Denpasar, 2024)
The tooth-cutting ceremony is one of the manusa yadnya ceremonies that must be lived in the life of Hindus to control the six enemies in humans ( sad ripu). This study wanted to know the impact of the tooth- cutting ceremony for the Balinese Hindu community in Klungkung Regency on HIV sufferers. The purpose of this study is to know. (1) The truth of the tooth-filing teaching in Hindu theology, 2) How the impact of the tooth- cutting ceremony in Klungkung Regency on HIV sufferers, in this study is the relationship between culture and theoretical input in the concept of carrying out tooth- cutting ceremonies in Klungkung Regency for HIV sufferers. This research is by qualitative method and data obtained by making observations including reading literature literature. Data is obtained through several stages: (1) observation of the object of research, so that documents in the form of photos / videos about the implementation of the tooth- cutting ceremony are obtained. (2) interviews were conducted with HIV sufferers and families who performed the tooth- cutting ceremony. Prejudice and public treatment of HIV sufferers is very positive where Hindu culture builds the self-confidence of HIV sufferers kikir.